A PROJECT REPORT OF THE 1954 TASK COMMITTEE ON INTERNAL AUDITING EDUCATION. - Cunningham, Earle H.; Meigs, Walter B.; Reither, Ambrose M.; Shors, William F.; Van Voorhis, Robert H. (The Accounting Review, 1955)
Abstract This article presents a project report of the 1954 task committee on internal auditing education. In 1951, the American Accounting Association set up a Committee on Cooperation with the Institute of Internal Auditors. As one of its first activities, this Committee conducted a survey of college courses in internal auditing. In view of the increasing interest in internal auditing courses evidenced by this survey, it seemed appropriate to give further thought to the place of the internal auditing course in the college curriculum, and the problems of organizing and establishing such a course, its content, and manner of presentation. In view of the present crowded condition of the undergraduate accounting curriculum and the much-discussed dangers of excessive specialization, a recommendation for the addition of a new course such as internal auditing cannot be given in a light or casual manner. As the large corporation becomes a more and more significant element in the economy, internal auditing is receiving increased recognition as a valuable aid to top corporate management.